IoT-based mobile data acquisition for pH and temperature monitoring as an enrichment material for high school energy transformation book - Amalia Hidayah; Maulana Firmansyah; Dwi Teguh Rahardjo; Anif Jamaluddin (Education and Development Research, 2026)
Monitoring pH and temperature is critical in various fields, yet integrating such technical concepts into high school education remains a challenge. This study aims to develop and validate an IoT-based mobile data acquisition system as a practical case study for an enrichment book on the topic of energy transformation for high school students. Using a Research and Development (R&D) approach, an IoT device consisting of a pH sensor, a K-type thermocouple, and a NodeMCU ESP8266 was built. An accompanying enrichment book was developed using Canva and Heyzine Flipbook. The IoT system demonstrated good accuracy, achieving R² values for pH measurement of 0.9526 (acidic) and 0.8843 (basic). The enrichment book was validated by experts and practitioners, receiving high feasibility ratings of 92.58% and 83.01%, respectively. These findings indicate that the developed enrichment book is a highly feasible supplementary teaching resource. This study demonstrates the significant potential of integrating hands-on IoT projects into science curricula to enhance students' understanding of abstract concepts like energy transformation.